Assessment of residential satisfaction with public housing in Hulhumale', Maldives - Mohit, Mohammad Abdul; Azim, Mohamed (Elsevier, 2012)
This paper assesses the residential satisfaction with public housing in Hulhumale’, Maldives, on physical features and service provision within the housing unit, public facilities and the social environment within the housing area and their contributions to residents’ overall housing satisfaction. The findings show that a majority of the residents are only slightly satisfied, though satisfaction levels were generally higher for services provided and public facilities, compared to satisfaction with physical space within the housing unit and the social environment within the housing area. The study infers that merely providing housing does not ensure success of existing housing development and policies.